Liver cirrhosis affects serum lactate level measurement while assessing disease severity in patients with sepsis. Issue 9 (September 2021) - Cheng, Chi-Yung; Kung, Chia-Te; Wu, Kuan-Han; Chen, Fu-Cheng; Cheng, Hsien-Hung; Cheng, Fu-Jen; Huang, Jyun-Bin; Su, Chih-Min
Abstract : Background: Elevated serum lactate is associated with higher mortality in sepsis, whereas liver dysfunction is associated with higher serum lactate levels. We assessed the predictive ability of serum lactate in patients with liver cirrhosis and sepsis. Methods: This retrospective study included 12 281 cases of suspected infection with initial serum blood lactate drawn during January 2007–December 2013. Results: Using one-to-two propensity score matching analysis, 1053 and 2106 septic patients with and without underlying liver cirrhosis, respectively, were successfully matched. Lactate levels of survivors and nonsurvivors were 2.58 and 5.93 mmol/L, respectively, in patients without liver cirrhosis (WLC), 2.96 and 7.29 mmol/L, respectively, in patients with nondecompensated liver cirrhosis (NDLC), and 4.08 and 7.16 mmol/L, respectively, in patients with decompensated liver cirrhosis (DLC). In receiver operating characteristic curve analysis, the sensitivity and specificity for predicting mortality were 0.81 and 0.55, respectively, in the WLC group, 0.85 and 0.45, respectively, in the NDLC group, and 0.86 and 0.33, respectively, in the DLC group, using serum lactate levels >2.0 mmol/L. Conclusions: The serum lactate level can be used to predict the severity of sepsis in patients with liver cirrhosis; however, its specificity would be lower at a cutoff of 2.0 mmol/L.